The role of informational technologies in creating a personalized customer experience: A case study of tourism branch in Ukraine - Dariia Basyuk; Tetyana Prymak; Nataliia Pohuda (CES Working Papers, 2018)
Personalizing relationships with clients for the tourism industry is an extremely important factor in the development and profit making, since communication in tourism involves close interaction with consumers and their individual requests and wishes. Ukrainian companies, that implement the principles of personalization often face the lack of scientifically based methods for preparing and adopting managerial decisions using modern information technologies. An analysis of the activities of domestic and foreign tourism enterprises regarding the personalization of relations with clients shows that at the present stage there is a tendency to switch from a strategy of concentrated marketing to a strategy of personalization, where each client is offered an individualized service complex. As a result of the scientific search, there have been offered various innovative ways and means of optimizing the work of tourism company managers for personalized interaction with customers through Internet technologies, which include modern analytics services, information collection and processing, as well as tools that allow the creation of personalized emails, promotional advertisement, content, etc. The integrated implementation of modern personalized marketing tools ensures effective and long-lasting relationships with customers, which is the key to the successful operation of the company's tour in the market.
Keywords: 330; marketing relations; IT-technologies; CRM systems; personalization